2010
DOI: 10.1186/1756-0500-3-138
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gene expression in Atlantic halibut (Hippoglossus hippoglossus L.) and its relation to egg quality

Abstract: BackgroundThe commercial production of Atlantic halibut (Hippoglossus hippoglossus L.) suffers from a major bottleneck due to the low success of producing juveniles for on-growing. Atlantic halibut females are routinely hand-stripped and incorrect timing of stripping can result in low quality eggs due to post-ovulatory aging. Post-ovulatory aging leads to compositional changes in eggs that include maternally provided proteins and RNAs. There have been few studies of the maternally provided mRNA transcripts tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…It also has been shown that specific genes show certain patterns of RNA degradation during early development and that maternal RNA is present (Wen et al 2005;Bai et al 2007;Ferg et al 2007). Furthermore, it has been demonstrated that the sudden decrease after germinal breakdown is characteristic for maternal genes (Mommens et al 2010). Studies in fish addressing this hypothesis are however limited.…”
Section: Introductionmentioning
confidence: 97%
“…It also has been shown that specific genes show certain patterns of RNA degradation during early development and that maternal RNA is present (Wen et al 2005;Bai et al 2007;Ferg et al 2007). Furthermore, it has been demonstrated that the sudden decrease after germinal breakdown is characteristic for maternal genes (Mommens et al 2010). Studies in fish addressing this hypothesis are however limited.…”
Section: Introductionmentioning
confidence: 97%
“…Bonnet et al (2007) showed that prohibitin 2 was negatively associated with development success in rainbow trout. In Atlantic halibut, two maternal genes (HHC00353 and HHC01517) correlated positively with hatching success and one gene (HHC00255) correlated negatively with the percentage of normal blastomeres (Mommens et al 2010). …”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, maternal transcripts may also function indirectly as a source of nutrition, providing nucleotides and phosphorus during the development (Shen-Orr et al 2010). Recent studies in rainbow trout (Oncorhynchus mykiss) and Atlantic halibut (Hippoglossus hippoglossus) have shown that some maternal mRNAs are differentially expressed in eggs of varying quality (Aegerter et al 2005;Bonnet et al 2007;Mommens et al 2010). For instance, high quality eggs were characterized by higher transcript levels of nucleoplasmin, tubulin β, and insulin-growth factor 1, and lower levels of keratins 8 and 18, cathepsin Z and prostaglandin synthase 2 in rainbow trout (Aegerter et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, species such as Atlantic halibut (Hippoglossus hippoglossus) have considerable potential for commercial production; however, hatching rates of less than 1% continue to obstruct the growth of the industry (Norberg et al, 1991;Mommens et al, 2011). Even in families such as the Salmonidae, where there has been considerable work on culture and incubation systems, egg mortality rates of up to 50% still occur (Bromage et al, 1992;Brooks et al, 1997;Bobe and Labbe, 2010).…”
Section: Introductionmentioning
confidence: 99%